DILEMA ISLAMIC STUDIES, DILEMA PENDIDIKAN ISLAM - Abdul Munir Mulkhan (EL-TARBAWI, 2002)
The developing of the Integrated Islamic School in recent years appears the problem especially the using of the term" integrated", besides, the conceptual problem and it is important to clarify and to solve the conceptual problem. The terminology of integrated can narrow Islam as a religion because Islam is only can be regarded as the knowledge of Islamic religion and the general knowledge is not Islamic knowledge. Departing from the discourse on the Integrated Islamic Education mentioned above, it should be placed the problem of the concept of ilm in Islam as diin. Based on the belief of the function of Islam as revelation can guide human life, it is clear that all knowledge /science constitute an Islamic knowledge/science that based on a truth principle and methodology. The right knowledge/science is Islam, whether the knowledge developed in Europe and America or the Middle East, and the wrong knowledge can be regarded as the disbelievers' knowledge. According to the author that the criteria of the right is in accordance with the law of universe and sacred texts and the high grade of the right is only dzanni, relative and probable.